2014
DOI: 10.1016/j.neulet.2014.08.040
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of lateral olivocochlear neurons with a dopaminergic neurotoxin depresses spontaneous auditory nerve activity

Abstract: Neurons of the lateral olivocochlear (LOC) system project from the auditory brainstem to the cochlea, where they synapse on radial dendrites of auditory nerve fibers. Selective LOC disruption depresses sound-evoked auditory nerve activity in the guinea pig, but enhances it in the mouse. Here, LOC disruption depressed spontaneous auditory nerve activity in the guinea pig. Recordings from single auditory nerve fibers revealed a significantly reduced proportion of fibers with the highest spontaneous firing rates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 48 publications
1
7
0
Order By: Relevance
“…When the LSO is lesioned in the guinea pig brainstem using melittin ( Le Prell et al, 2003b ) or the LOC system is lesioned in the guinea pig cochlea using MPTP ( Le Prell et al, 2005 ), sound-driven AN activity is decreased. When the guinea pig LOC system is lesioned using MPTP, spontaneous AN firing is also decreased ( Le Prell et al, 2014a ). We have long speculated that the decreases in spontaneous and sound driven AN firing after OCB transection, LSO lesion, or LOC lesion could be the result of compromised CGRP release when the LOC system is disrupted ( Le Prell et al, 2003b ; Le Prell et al, 2005 ; Le Prell, 2007 ; Le Prell et al, 2014a ).…”
Section: Discussionmentioning
confidence: 99%
“…When the LSO is lesioned in the guinea pig brainstem using melittin ( Le Prell et al, 2003b ) or the LOC system is lesioned in the guinea pig cochlea using MPTP ( Le Prell et al, 2005 ), sound-driven AN activity is decreased. When the guinea pig LOC system is lesioned using MPTP, spontaneous AN firing is also decreased ( Le Prell et al, 2014a ). We have long speculated that the decreases in spontaneous and sound driven AN firing after OCB transection, LSO lesion, or LOC lesion could be the result of compromised CGRP release when the LOC system is disrupted ( Le Prell et al, 2003b ; Le Prell et al, 2005 ; Le Prell, 2007 ; Le Prell et al, 2014a ).…”
Section: Discussionmentioning
confidence: 99%
“…Because the MOC projection is myelinated and the LOC projection is not, stimulation of the IVth floor of the ventricle also predominately activates the MOC pathway. However, it is possible to selectively disrupt the LOC pathway using a neurotoxin and Le Prell et al ( 2014a ) found that disruption of LOC neurons depressed spontaneous cochlear nerve activity. When the CGRP component of the LOC system was eliminated, the loss of CGRP caused reduced cochlear nerve activity and resulted in increased 50% PPI thresholds in quiet and in background noise.…”
Section: Discussionmentioning
confidence: 99%
“…Loss of either the MOC or LOC system after cochlear development does not affect auditory thresholds, yet both systems are activated by sound. Sound suppresses MOC responses (as assessed by otoacoustic emissions and cochlear action potentials and nerve activity) and CGRP transmission through the LOC system has been shown to enhance suprathreshold cochlear nerve activity suggesting that both systems may work in tandem to enhance behavioral responses to sound (Maison et al, 2002 , 2003a ; Guinan et al, 2005 ; Guinan, 2006 , 2010 , 2013 , 2014 ; Le Prell et al, 2014a , b ; Dickerson et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…In other words, the effect of damaging LOC parent neurons on auditory nerve responses seems to be species specific. Disruption of LOC efferents with a dopaminergic neurotoxin depresses the spontaneous activity of auditory nerve fibers in guinea pig ( 73 ).…”
Section: Anatomy and Physiology Of Olivocochlear Efferents In Animalsmentioning
confidence: 99%